2002
DOI: 10.1111/j.1467-842x.2002.tb00274.x
|View full text |Cite
|
Sign up to set email alerts
|

Infectious Disease: The risk of Ross River and Barmah Forest virus disease in Queensland: Implications for New Zealand

Abstract: Objectives: To describe the incidence of Ross River (RR) and Barmah Forest (BF) virus disease in Queensland and determine the risk of importation of RR virus from Queensland into New Zealand (NZ) via viraemic travellers. Methods: Based on routine RR and BF virus notification data of seven major urban tropical and subtropical Queensland populations, incidence rates adjusted for age, sex, season and a baseline level of immunity were used to examine the annual and seasonal risk of disease in the specific populati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 29 publications
2
40
0
Order By: Relevance
“…RRV is a small, enveloped, positivesense single-stranded RNA virus transmitted by mosquitoes (2,3). RRV disease (RRVD) in humans commonly affects the ankles, knees, and peripheral joints.…”
mentioning
confidence: 99%
“…RRV is a small, enveloped, positivesense single-stranded RNA virus transmitted by mosquitoes (2,3). RRV disease (RRVD) in humans commonly affects the ankles, knees, and peripheral joints.…”
mentioning
confidence: 99%
“…18 Kelly-Hope et al estimated that each year more than 100 people entered New Zealand from Queensland, Australia, with clinical or subclinical infections of RRV. 19 The risk of local transmission is greatly increased by the presence of another Australian mosquito well established in New Zealand: Oc hlerotatus (Finlaya) notoscriptus Skuse. Laboratory transmission studies in New Zealand have indicated that Oc.…”
Section: Article Environmental Healthmentioning
confidence: 99%
“…This likelihood is increased by New Zealand's large urban and periurban populations of Brushtail possums (Trichosurus vulpecula), which are competent intermediate hosts of RRV. 19,26 The population of possums now occupies more than 95% of New Zealand's land area and it is estimated to be as large as 70 million. 27 The presence of wallabies (Macropus spp.)…”
Section: Article Environmental Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…In spite of a regular influx of viremic travellers, particularly from Australia (Kelly-Hope et al 2002;Derraik & Calisher 2004), only a single mosquito-borne virus circulating in New Zealand has been isolated (Holder et al 1999;Crump et al 2001). The Sindbis-like alphavirus Whataroa virus, also detected in Australia (Saleh et al 2004), but in New Zealand known only from the area around the town of Whataroa on the west coast of the South Island, was first detected in bird populations there in 1962 (Ross et al 1964;Maguire et al 1967).…”
Section: Introductionmentioning
confidence: 99%